The effect of turmeric extract on the physiological responses of golden dragon fruit during postharvest storage - Handoko; Ayu Purnamasari; Alfassabiq Khairi (Talenta Publisher, 2026)
Golden dragon fruit (Hylocereus megalanthus L.) is an economically important tropical fruit belonging to climbing cacti, which are well adapted to tropical and subtropical environments and exhibit high drought tolerance. Despite its commercial value and nutritional benefits, postharvest quality deterioration remains a major challenge, leading to significant losses in texture, flavor, aroma, and shelf life. Turmeric (Curcuma longa L.) extract has been reported to possess antimicrobial and bioactive compounds, particularly curcuminoids, which may contribute to the preservation of fruit quality during storage. This study aimed to determine the optimal concentration of turmeric extract and to evaluate its effects on the postharvest quality of golden dragon fruit. The experiment was conducted in March 2025 at PT Daya Semesta Agro Persada, Banyuasin Regency, South Sumatra, Indonesia. Fruits were harvested at 30 days after anthesis and stored under controlled conditions at 26.50 ± 1.02 °C and 75.77 ± 5.45% relative humidity, with individual weights ranging from 350 to 500 g. A Completely Randomized Design with four replications was employed, and treatments consisted of turmeric extract dissolved in distilled water at concentrations of 0, 5, 10, and 15 g L⁻¹. Observed parameters included fruit texture, flavor, aroma, physiological weight loss, fruit decay (rotting), and shelf life. Results indicated that golden dragon fruits treated with the highest concentration of turmeric extract (15 g L⁻¹) and stored for nine days exhibited superior retention of texture, flavor, and aroma. Furthermore, this treatment significantly reduced physiological weight loss and fruit decay while effectively extending shelf life compared with lower concentrations and the control. The findings suggest that turmeric extract at 15 g L⁻¹ is an effective postharvest treatment to maintain quality and prolong the shelf life of golden dragon fruit, providing practical implications for commercial production and storage management.